Dinamika Kebijakan REDD+ Di Kalimantan Tengah: Dari Implementasi Awal (2007–2012) Hingga Reaktivasi Tahun 2025: REDD+ Policy Dynamics in Central Kalimantan: From Initial Implementation (2007–2012) to Reactivation in 2025 - Jemi, Renhart; Manuri, Solichin; Afentina, Afentina; Harinie, Luluk Tri; Perdana, Indra; Anshari, Rifqi; Yoyo, Yoyo; Minarni, Tri; Jagau, Yanedi; Uthan, Lyra Asaria; Sukarna, Raden Mas; Wahyudi , Wahyudi (JURNAL HUTAN TROPIKA, 2025)
ABSTRACTS The Reducing Emissions from Deforestation and Forest Degradation (REDD+) Program is a global initiative aimed at reducing carbon emissions from the forestry sector. Central Kalimantan has served as a pilot province for REDD+ implementation in Indonesia since 2007 through various initiatives led by the government and international organizations. This study aims to analyze the initial implementation dynamics of REDD+ in Central Kalimantan in 2007, focusing on policies, implementing actors, and key challenges encountered. The research applies a descriptive qualitative approach, using literature review and policy document analysis. The results indicate that the period 2007–2012 was the readiness phase, during which institutional and policy frameworks were developed; the period 2013–2014 marked the implementation phase; and the period 2016 to the present represents the result-based payment phase. However, the early implementation faced several major challenges, including limited inter-agency coordination, low technical capacity, and weak synchronization between national and regional policies. Despite these obstacles, the early stage of REDD+ implementation in Central Kalimantan has provided an important foundation for the future development of climate and forest governance policies in Indonesia. KEYWORDS: Carbon Emissions, Program Implementation, Central Kalimantan, Forestry Policy, REDD+